Step-by-step explanation:
I assume the original expression is
2x² + 16x + 11
we need to get this into the form of a(x + b)² + c
let's do the generic multiplication and compare the result to the given expression :
a(x² + 2bx + b²) + c = ax² + 2abx + ab² + c
when we compare this with the original equation, we only need to look at terms with the same variable exponents.
2x² is the only term with "x²".
and ax² is the only term with "x²" in the generic form.
so ?
2x² = ax²
=>
a = 2
16x is the only term with "x" (exponent 1).
2abx is the only term with "x" in the generic form.
16x = 2abx
8x = abx = 2bx
4x = bx
=>
b = 4
11 is the only pure number (constant).
ab² + c is the only constant term in the genetic form.
11 = ab² + c = 2×4² + c = 2×16 + c = 32 + c
-21 = c
so, the solution is
2(x + 4)² - 21